Kitchen capitalism : microenterprise in low-income households - Sherraden, Margaret S.; Sanders, Cynthia K., 1964-; Sherraden, Michael W. (Michael Wayne), 1948- (Albany : State University of New York Press, 2004)
"Businesses come to life as owners are allowed to speak in their own words in this first in-depth examination of self-employment told from the perspectives of low-income microentrepreneurs. The book systematically analyzes a range of issues, including who chooses to open a micro business, and why; what resources to they bring to their business venture; how well will their venture fare; and what contributes to the growth or decline of their business."--Jacket
Little businesses, large hopes -- Theory and evidence -- Who wants to be a microentrepreneur and why? -- Getting started : resources for microenterprise -- The bottom line : business and household -- Microenterprise performance -- Beyond profit : multiple outcomes of microenterprise -- Fighting poverty or promoting development?
Includes bibliographical references (pages 245-263) and index.
Print version record.
JSTOR
Keywords: Self-employed -- United States; Poor -- Employment -- United States; Entrepreneurship -- United States; Small business -- United States; Travailleurs indépendants -- États-Unis.; Pauvres -- Travail -- États-Unis.; Entrepreneuriat -- États-Unis.; Microentreprises -- États-Unis.; BUSINESS & ECONOMICS -- Small Business; Entrepreneurship; Poor -- Employment; Self-employed; Small business; United States; Selbstständiger; Armut; Niedriglohn; Kleinunternehmer; USA